Karakteristik Pasien Diabetes Melitus dengan Pengetahuan Tentang Hipoglikemia - Divianty, Rika; Diani, Noor; Nasution, Tina Handayani (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2021)
Diabetes mellitus is a problem that can cause short-term complications, one of them is hypoglycemia.Hypoglycemia is a complicating factor for achieving normal blood glucose levels. To avoid the complicationsof good hypoglycemia, adequate knowledge is needed so that sufferers can prevent complications. This studyanalyzed the correlation between characteristics of patients with diabetes mellitus through knowledge abouthypoglycemia at Cempaka Inpatient Community Health Center with cross sectional approach. The samplingtechnique was consecutive sampling with a total sampling of 64 type 2 diabetes mellitus patients. Data wereanalyzed by using Chi Square test. The results also showed that most patients with diabetes mellitus associatedwith knowledge about age hypoglycemia (p-value = 0.017), length of suffering (p-value = 0.020), education (pvalue = 0.042), and those not related to sex (p-value = 0.149), and occupation (p-value = 0.380).Characteristics of diabetes mellitus patients become a support for knowledge about hypoglycemia because ofthese characteristics are expected to achieve an understanding of the actions to be taken in an effort to improvethe complications of hypoglycemia